A novel biohydrogen production process: Co-digestion of vinasse and Nejayote as complex raw substrates using a robust inoculum. (2nd March 2017) - García-Depraect, Octavio; Gómez-Romero, Jacob; León-Becerril, Elizabeth; López-López, Alberto
Abstract: The main drawback of biohydrogen (bioH2 ) production by mono-digestion of vinasse and maize processing wastewaters ( Nejayote ) is related to high recalcitrance, unbalanced nutrients and unsuitable alkalinity. A novel co-digestion process of vinasse and Nejayot e was proposed to overcome this problem. The effects of different vinasse/ Nejayote ratios (i.e. 100/0, 80/20, 60/40, 40/60, 20/80 and 0/100 w/w, respectively) on bioH2 production were evaluated in a batch reactor at 35 °C, pH 5.5. Microbial community shifts were also analyzed via Illumina MiSeq sequencing. The results showed that the maximum bioH2 production rate of 107 NmL H2 /Lr h and bioH2 yield of 115 NmL H2 /g TVSadded were achieved at a vinasse/ Nejayote ratio of 80/20. Vinasse and Nejayote were complementary in the concentrations of nitrogen, iron, magnesium, phosphorus and alkalinity. Acetobacter orientalis predominated in the inoculum (42.94%). However, at the exponential phase it was replaced by Lactobacillus casei, Clostridium beijerinckii, Acetobacter lovaniensis and Sporolactobacillus terrae with abundances of 22.03%, 20.27%, 13.39% and 12.96%, respectively. A syntrophy between lactic and acetic acid bacteria, and bioH2 producers was established. Metabolic profiles showed that bioH2 and butyrate were produced from acetate and lactate. The microbial structure of the inoculum allowed adaptability to feed the substrates, indicating a high robustness. Thus, it could be employed for bioH2 production from some other complex substrates. In conclusion, co-digestion of vinasse and Nejayote enhanced the overall bioH2 production because of their mutual complementarity. Graphical abstract: Highlights: A novel co-digestion process of vinasse and Nejayote was proposed to produce bioH2 . BioH2 and butyrate were produced from lactate and acetate. The highest VHPR of 107 NmL/Lr h and bioH2 yield of 115 NmL/g VSadded were achieved. Lactic and acetic acid bacteria coexist with the bioH2 producing consortium. Co-digestion saved base addition up to 46% and provided enough nutrients.